RELASI PENYELENGGARAAN PERADILAN PIDANA YANG CEPAT, SEDERHANA DAN BIAYA MURAH TERHADAP PELAKSANAAN PIDANA CAMBUK DI NANGROE ACEH DARUSSALAM: KONSTRUKSI TERHADAP PEMBAHARUAN RUU KUHP - Safik Faozi; Rochmani; Wenny Megawati (Jurnal Komunikasi Hukum, 2022)
Article 2 paragraph 4 of Law no. 48 of 2009 concerning Judicial Powers of Punishment states that trials are carried out in a simple, fast and low cost manner. This principle has been implemented in the implementation of the imposition of caning in Aceh. The implementation is in an open field and ends in 1 day. It is interesting to study from the principles of fast, simple, and low-cost justice. The execution of the caning sentence which ends in 1 day embodies the principle of a fast trial, carried out in the open field by wearing a certain size of rattan, showing a simple trial. The implementation also demonstrates the principle of low-cost justice. In the perspective of the Criminal Code Bill, the implementation of this punishment is based on living law and has been stated in the applicable law in Aceh, realizing the criminal objectives of prevention, fostering perpetrators, restoring balance, and resolving conflicts. Its rationality rests on the laws that live in Aceh, and embodies the principles of fast, simple and low-cost justice. Philosophically, this punishment is built on the basis of the Acehnese people's view of life which relies on philosophical values ​​derived from Islamic law. Sociologically, caning has been around for a long time in Acehnese society. Juridically normative based on the 1945 Constitution, the implementation of caning reflects the law that lives in society as an embodiment of customary units that apply in Acehnese society as stipulated in Article 18 B.